Freshwater fishing - Gale, Ryan (The Child's World, 2024)
"Explores the techniques and equipment needed for freshwater fishing, provides background information on fishing regulations, and covers guidelines for safety and conservation. Additional features include a table of contents, sidebars, infographics, Fast Facts, critical thinking questions, a phonetic glossary, an index, and sources for further research"--
Grades 4-6